2014
DOI: 10.9753/icce.v34.waves.17
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Simulation of Instantaneous Nearshore Water Levels During Typhoons

Abstract: 3D hydrodynamic simulations were performed on an area extending 600 km off Taiwan island for the period running from September 2011 to December 2012. We covered a winter Monsoon season and a summer season with 17 typhoons recorded. By comparing simulations and measurements during the TALIM typhoon, our model reproduces correctly the storm surge observed along the Wan-Tzu-Liao sand barrier (South-West Taiwan). By a modelling approach, we analyzed the regional hydrodynamic mechanisms which control the sea surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A first strategy relies on unstructured grids together with finite volume or finite element discretizations; numerous models such as Delft3D (Roelvink and van Banning, 1995), SLIM (Delandmeter et al, 2018), TELEMAC-3D (Janin et al, 1993) or T-UGOm (Piton et al, 2020) have shown their capability to cope with complex geometrical features such as river deltas or continental slope for years. A second strategy is based on curvilinear, either orthogonal (Rétif et al, 2014;Diaz et al, 2020;Marsaleix et al, 2006; among many others) or nonorthogonal (Grasso et al, 2018), grids. However, the design of such grids might be a great deal of work and have a lack of flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…A first strategy relies on unstructured grids together with finite volume or finite element discretizations; numerous models such as Delft3D (Roelvink and van Banning, 1995), SLIM (Delandmeter et al, 2018), TELEMAC-3D (Janin et al, 1993) or T-UGOm (Piton et al, 2020) have shown their capability to cope with complex geometrical features such as river deltas or continental slope for years. A second strategy is based on curvilinear, either orthogonal (Rétif et al, 2014;Diaz et al, 2020;Marsaleix et al, 2006; among many others) or nonorthogonal (Grasso et al, 2018), grids. However, the design of such grids might be a great deal of work and have a lack of flexibility.…”
Section: Introductionmentioning
confidence: 99%